Beneficial Ownership in the Sharī‘ah and Modern Law: A Case of Sovereign and Quasi-Sovereign Ijārah Ṣukūk Structures in Pakistan, Bahrain, and Malaysia - Muhammad Shoaib Cheema; Muhammad Tahir Mansoori; Imam Uddin; Abdul Karim Usman (Islamic Banking and Finance Review, 2021)
The concept of beneficial ownership has been used extensively in sovereign and quasi-sovereign ijārah ṣukūk structuring. This paper aims to examine the concept of beneficial ownership in the light of Islamic jurisprudence, common law and civil law systems. It overviews the laws related to beneficial ownership in the Pakistani, Bahraini, and Malaysian legal regimes. It further carries out the Sharīʿah appraisal of beneficial ownership focusing on its chief characteristics. The findings of this study posit that the legal status of ownership as per the Sharī‘ah is a need-based phenomenon and not a mandatory requirement. Hence, if a particular transaction complies with the ahkam (commands) for milkiyah and tamlikat (ownership), then transfer of ownership is a compulsory element for sale consequences. Moreover, it also explains that the use of beneficial ownership in sovereign and quasi-sovereign ijārah ṣukūk structures is acceptable in principle because the valid sale transaction that occurs transfers the ownership to the latter. Hence, it is described in ṣukūk prospectuses as ‘beneficial interest’. Finally, it may also be justifiable in the context of of ḥurīat al-taṣarruf (right to dispose-off the asset) and ‘qualified ownership’.Keywords Beneficial Ownership (BO), Ijārah Sukūk (IS), Legal Title (LT), Sharī‘ah Appraisal (SA)